MGA Mutation as a Novel Biomarker for Immune Checkpoint Therapies in Non-Squamous Non-Small Cell Lung Cancer - Sun, Lei; Li, Man; Deng, Ling; Niu, Yuchun; Tang, Yichun; Wang, Yu; Guo, Linlang (Frontiers in Pharmacology, 2021)
Background: Immune checkpoint inhibitors have changed the treatment landscape for advanced non-small cell lung cancer. However, only a small proportion of patients experience clinical benefit from ICIs. Thus, the discovery of predictive biomarkers is urgently warranted. Evidence have shown that genetic aberrations in cancer cells can modulate the tumor immune milieu. We therefore explored the association between oncogenic mutations and efficacy to ICIs in non-squamous NSCLC. Methods: We curated genomic and clinical data of 314 non-squamous NSCLC patients receiving ICIs from four independent studies for the discovery cohort. For external validation, 305 patients from an ICI-treated cohort and 1027 patients from two non-ICI-treated cohorts were used. Relations between oncogenic mutations and outcomes of immunotherapy were examined. Multivariate Cox regression models were applied to adjust confounding factors. Further investigation on tumor antigenicity and antitumor immunity was performed in The Cancer Genome Atlas lung adenocarcinoma cohort. Results: A total of 82 oncogenes/tumor suppressor genes according to the Oncology Knowledge Base database with a frequency greater than 3% were identified and investigated in the discovery cohort. Within these genes, MGA mutations were enriched in patients with durable clinical benefit (p = 0.001, false discovery rate q < 0.05). The objective response rate was also significantly higher in patients with MGA mutation (2.63-fold, p < 0.001, FDR q < 0.05). Longer progression-free survival was found in MGA-mutated patients (HR, 0.41; 95% CI, 0.23-0.73; p = 0.003), and the association remained significant after controlling for tumor mutational burden (TMB), programmed cell death ligand-1 expression, and treatment regimens. In the validation cohort, significant improvement in overall survival was found in patients harboring MGA mutation (HR, 0.39; 95% CI, 0.17-0.88; p = 0.02). Furthermore, the survival difference was not detected in non-ICI-treated cohorts. We also demonstrated that MGA mutation correlate with higher TMB, elevated neoantigen load and DNA damage repair deficiency. Gene set enrichment analysis revealed that gene sets regarding activated immune responses were enriched in MGA-mutated tumors. Conclusions: Our work provides evidence that MGA mutation can be used as a novel predictive biomarker for ICI response in non-squamous NSCLC and merits further clinical and preclinical validation.